Active material layer for negative electrode and method for manufacturing the same, electrode mixture paste for negative electrode of power storage device, negative electrode for power storage device, and power storage device
The use of silicon particles with a polyimide binder in the negative electrode active material layer addresses the challenge of maintaining high capacity and cycle stability by absorbing volume changes, enhancing the performance of power storage devices.
Patent Information
- Application Number
- JP2024192541
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-10-02
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional binders like polyvinylidene fluoride or rubber-based resins fail to maintain both high capacity and excellent cycle characteristics in negative electrodes due to volume changes during charging and discharging, leading to interface peeling and decreased performance in industrial applications.
A negative electrode active material layer using silicon particles with an average diameter of less than 10 μm, combined with a polyimide binder having a porosity of less than 20%, formed with a polyamic acid precursor, which is an organic polymer with imide bonds in the main chain, to absorb volume expansion and enhance mechanical stability.
The solution achieves high charging and discharge capacity while maintaining excellent cycle characteristics, ensuring the negative electrode's durability and efficiency in power storage devices.
Smart Images

Figure 2025013438000001 
Figure 2025013438000002 
Figure 2025013438000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material layer and a method for producing the same, an electrode mixture paste for a negative electrode of an electricity storage device, a negative electrode for an electricity storage device, and an electricity storage device. [Background technology]
[0002] An energy storage device is a device that can store electrical energy when needed and extract the energy when needed. Representative energy storage devices include secondary batteries such as lithium-ion secondary batteries, which are widely used as driving power sources for mobile information terminals. In recent years, development of high-capacity energy storage devices has been promoted with a view to expanding into industrial applications such as electric and hybrid vehicles and unmanned aerial vehicles. One of the attempts is to increase the charge and discharge capacity by using, for example, silicon or tin, which have a large lithium absorption capacity per unit volume, or an alloy containing these, as the negative electrode active material of the energy storage device.
[0003] However, active materials with large charge / discharge capacities, such as silicon, tin, or alloys containing these, undergo a very large volume change during charging and discharging. If general-purpose binders such as polyvinylidene fluoride or rubber-based resins are used in electrodes containing such active materials, the volume change can cause destruction of the active material layer or peeling at the interface between the current collector and the active material layer, resulting in a problem of reduced cycle characteristics of the electricity storage device.
[0004] As a method for solving this problem, a method has been proposed in which silicon particles having an average particle size of 1 to 10 microns are bound together using polyimide, which has excellent mechanical properties, and then subjected to a thermal pressure treatment to form a negative electrode active material layer (Patent Documents 1 to 5).
[0005] It has been pointed out that in a negative electrode using the polyimide disclosed in the above patent document as a binder, cracks are generated in the active material layer when the electrode is charged and discharged, forming an island structure with spaces that can absorb the volume expansion during charging, thereby improving the capacity retention rate during repeated charging and discharging (Non-Patent Document 1). Recently, negative electrodes that focus on the shape of the active material layer have also been studied (Patent Document 6). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2004 / 004031 [Patent Document 2] JP 2004-235057 A [Patent Document 3] JP 2003-203637 A [Patent Document 4] JP 2004-288520 A [Patent Document 5] JP 2004-022433 A [Patent Document 6] JP 2017-092048 A [Non-patent literature]
[0007] [Non-Patent Document 1] Proceedings of the 48th Battery Symposium, 2B23, p.238 (2007) (Yasushi Takano et al.) Summary of the Invention [Problem to be solved by the invention]
[0008] However, in the case of negative electrodes using the conventional polyimides as binders, it was sometimes difficult to achieve both high capacity and excellent cycle characteristics in industrial applications such as electric and hybrid vehicles.
[0009] Further, when the inventors conducted further tests, the negative electrode of Patent Document 6 was only able to maintain a discharge capacity ratio of 0.9 after 10 cycles in terms of cycle characteristics based on the second discharge and charge capacity. This means that merely specifying the porosity has not yet achieved both a high capacity sufficient for practical industrial use and excellent cycle characteristics.
[0010] Therefore, the present invention is intended to solve the above-mentioned problems, and has an object to provide an electrode mixture paste for a negative electrode of an electricity storage device, which is capable of achieving both high charge / discharge capacity and excellent cycle characteristics, a negative electrode active material layer, a negative electrode for an electricity storage device, and an electricity storage device. [Means for solving the problem]
[0011] The present invention relates in particular to the following items: 1. Silicon-based particles that contain silicon as an ingredient and can absorb and release lithium ions; A polyimide binder, which is an organic polymer with imide bonds in the main chain, and having a porosity of less than 20%. 2. The negative electrode active material layer according to item 1, wherein the silicon-based particles have an average particle size of less than 10 μm. 3. The negative electrode active material layer according to item 1 or 2, wherein the amount of the polyimide-based binder is 30 mass % or less based on the total mass of the negative electrode active material layer. 4. The negative electrode active material layer according to any one of items 1 to 3, wherein the precursor for forming the polyimide-based binder is a polyamic acid containing a repeating unit represented by the following chemical formula (I): [ka] (In the formula, A is one or more selected from the group consisting of tetravalent groups obtained by removing a carboxyl group from an aromatic tetracarboxylic acid, tetravalent groups obtained by removing a carboxyl group from an aliphatic tetracarboxylic acid, and tetravalent groups obtained by removing a carboxyl group from an alicyclic tetracarboxylic acid, and B is one or more selected from the group consisting of divalent groups obtained by removing an amino group from an aromatic diamine, divalent groups obtained by removing an amino group from an aliphatic diamine, and divalent groups obtained by removing an amino group from an alicyclic diamine.) 5. An electrode mixture paste for a negative electrode of an electricity storage device, used for forming the negative electrode active material layer according to any one of items 1 to 4 above. 6. A method for producing a negative electrode active material layer, comprising casting or applying the electrode mixture paste for a negative electrode of an electricity storage device according to item 5 onto a current collector, and subjecting the resulting product to a heat treatment. 7. A negative electrode for an electricity storage device, comprising the negative electrode active material layer according to any one of items 1 to 4 above. 8. An electricity storage device having the negative electrode for an electricity storage device according to item 7 above. Effect of the Invention
[0012] The present invention can provide a negative electrode active material layer that has high charge / discharge capacity and also has excellent cycle characteristics, a method for producing the same, an electrode mixture paste for an electricity storage device negative electrode, an electricity storage device negative electrode, and an electricity storage device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] <<Negative electrode active material layer>> The negative electrode active material layer according to one embodiment of the present invention contains silicon particles that contain silicon as a component and can store and release lithium ions, and a polyimide binder that is an organic polymer having imide bonds in the main chain. In addition, the negative electrode active material layer according to the present invention is characterized in that the porosity is less than 20%.
[0014] (Polyimide binder) The polyimide-based binder contained in the negative electrode active material layer of the present invention is an organic polymer having an imide bond in the main chain. The polyimide-based binder is not particularly limited, and a known polyimide-based binder used for an electrode binder may be used. Specific examples include organic polymers having an imide bond in the main chain, such as polyimide, polyamideimide, and polyesterimide. In the present invention, a material for forming the "polyimide-based binder" in the negative electrode active material layer is called a "precursor", and a material containing the "precursor", a solvent, and other compounds as necessary is called a "precursor composition". The precursor composition is sometimes called a "varnish".
[0015] The "precursor" is an organic polymer having an imide bond in the main chain, or a polymer or compound that can form an organic polymer having an imide bond in the main chain by heating or chemical reaction. Examples of the "precursor" that is an organic polymer having an imide bond in the main chain include polyimide, polyamideimide, polyesterimide, etc., which are generally used in the form of a precursor composition (varnish) dissolved in a solvent. These may be the same as the organic polymer that is the "polyimide-based binder", or may have a low imidization rate or a low molecular weight. Examples of the "precursor" that is a polymer or compound that can form an organic polymer having an imide bond in the main chain by heating or chemical reaction include polyamic acid, etc. These are also generally used in the form of a precursor composition (varnish) dissolved in a solvent. The amic acid portion of the polyamic acid may be partially imidized. The organic polymer that is the "polyimide-based binder" does not have to be completely imidized.
[0016] Such polyimide-based binders or precursors may be used alone or in combination of two or more. In the technical field, the "precursor" or "precursor composition" may also be called "binder", and in the following description, the "precursor" may also be called "polyimide-based binder", but it is clear from the context in which the term is used whether it refers to the precursor or the polyimide-based binder in the negative electrode active material layer.
[0017] For example, as a precursor capable of forming an organic polymer having an imide bond in the main chain by heating or chemical reaction, a polyamic acid, particularly a polyamic acid containing a repeating unit represented by the following chemical formula (I), is preferred.
[0018] [ka] (In the formula, A is one or more selected from the group consisting of tetravalent groups obtained by removing a carboxyl group from an aromatic tetracarboxylic acid, tetravalent groups obtained by removing a carboxyl group from an aliphatic tetracarboxylic acid, and tetravalent groups obtained by removing a carboxyl group from an alicyclic tetracarboxylic acid, and B is one or more selected from the group consisting of divalent groups obtained by removing an amino group from an aromatic diamine, divalent groups obtained by removing an amino group from an aliphatic diamine, and divalent groups obtained by removing an amino group from an alicyclic diamine.)
[0019] For example, a precursor that is an organic polymer having an imide bond in the main chain is preferably a polyimide that contains a repeating unit represented by the following chemical formula (II).
[0020] [ka] (In the formula, X1 is one or more selected from the group consisting of a tetravalent group obtained by removing a carboxyl group from an aromatic tetracarboxylic acid, a tetravalent group obtained by removing a carboxyl group from an aliphatic tetracarboxylic acid, and a tetravalent group obtained by removing a carboxyl group from an alicyclic tetracarboxylic acid, and Y1 is one or more selected from the group consisting of a divalent group obtained by removing an amino group from an aromatic diamine, a divalent group obtained by removing an amino group from an aliphatic diamine, and a divalent group obtained by removing an amino group from an alicyclic diamine.)
[0021] A precursor for forming such a polyimide-based binder can be prepared by a known method from a tetracarboxylic acid component having the A structure of chemical formula (I) or the X1 structure of chemical formula (II), a diamine component having the B structure of chemical formula (I) or the Y1 structure of chemical formula (II), and other components as necessary as essential components.
[0022] The tetracarboxylic acid component is not particularly limited and can be appropriately selected in consideration of the porosity of the target negative electrode active material layer and the desired characteristics of the power storage device. Examples of the tetracarboxylic acid component include 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, benzophenonetetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, diphenylsulfonetetracarboxylic dianhydride, p-terphenyltetracarboxylic dianhydride, m-terphenyltetracarboxylic dianhydride, and the like. Aromatic tetracarboxylic dianhydrides such as carboxylic dianhydrides, cyclobutane-1,2,3,4-tetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, dicyclohexyl-3,3',4,4'-tetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic acid-1,2:4,5-dianhydride, bicyclo[2.2.2]oct-7-ene-2,3:5,6-tetracarboxylic dianhydride and other alicyclic tetracarboxylic acids Dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3'-(hexafluoroisopropylidene)diphthalic anhydride, 5,5'-[2,2,2-trifluoro-1-[3-(trifluoromethyl)phenyl]ethylidene]diphthalic anhydride, 5,5'-[2,2,3,3,3-pentafluoro-1-(trifluoromethyl)pyropyridene]diphthalic anhydride, 1H-difuro[3,4-b:3',4'-i]xanthene-1,3,7 Suitable examples of the tetracarboxylic acid dianhydride include halogen-substituted tetracarboxylic acid dianhydrides such as 1,9(11H)-tetrone, 5,5'-oxybis[4,6,7-trifluoro-pyromellitic anhydride], 3,6-bis(trifluoromethyl)pyromellitic dianhydride, 4-(trifluoromethyl)pyromellitic dianhydride, 1,4-difluoropyromellitic dianhydride, and 1,4-bis(3,4-dicarboxytrifluorophenoxy)tetrafluorobenzene dianhydride. These may be used alone or in combination.
[0023] The diamine component is not particularly limited, and can be appropriately selected in consideration of the porosity of the target negative electrode active material layer and the desired characteristics of the power storage device. Examples of the diamine component include aromatic diamines such as p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 2,4-toluenediamine, 3,3'-dihydroxy-4,4'-diaminobiphenyl, bis(4-amino-3-carboxyphenyl)methane, and 2,4-diaminotoluene, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,3,5,6-tetrafluoro-1,4-diaminobenzene, 2,4,5,6-tetrafluoro-1,3-diaminobenzene, and 2,3,5,6-tetrafluoro-1,4-benzene(dimethane). Preferred examples of the diamines include halogen-substituted diamines such as 2,2'-difluoro(1,1'-biphenyl)-4,4'-diamine, 4,4'-diaminooctafluorobiphenyl, 2,2-bis(4-aminophenyl)hexafluoropropane, and 4,4'-oxybis(2,3,5,6-tetrafluoroaniline), and aliphatic or alicyclic diamines such as trans-1,4-diaminocyclohexane, cis-1,4-diaminocyclohexane, 1,6-hexamethylenediamine, 1,10-decamethylenediamine, 1,3-bis(aminomethyl)cyclohexane, and 1,4-bis(aminomethyl)cyclohexane. These may be used alone or in combination.
[0024] In terms of mechanical strength, battery characteristics, etc., in chemical formula (I) or chemical formula (II), it is preferable that X1 contains a tetravalent group obtained by removing a carboxyl group from an aromatic tetracarboxylic acid having a group that gives a bent structure, such as an ether bond. In particular, it is preferable that all of X1 and Y1 contain an aromatic group. In another embodiment, in terms of flexibility, formability of the negative electrode active material layer, battery characteristics, etc., it is preferable that Y1 contains an aliphatic group in chemical formula (I) or (II). In particular, it is preferable that X1 contains an aromatic group and that Y1 contains about 30 to 80 mol % of an aliphatic group.
[0025] Commercially available precursor products that can be used include, for example, UPIA (registered trademark)-AT, UPIA (registered trademark)-ST, UPIA (registered trademark)-NF, and UPIA (registered trademark)-LB manufactured by Ube Industries, Ltd.
[0026] The molar ratio of the tetracarboxylic acid component and the diamine component constituting the polyamic acid and / or polyimide used in the present invention [tetracarboxylic acid component / diamine component] can be set to be approximately equimolar, specifically 0.95 to 1.05, preferably 0.97 to 1.03. By setting the molar ratio within this range, the molecular weight of the obtained polyimide is high, and it is often possible to ensure the toughness when used as a binder. In addition, the polyamic acid and / or polyimide used in the present invention has a high molecular weight, with a logarithmic viscosity measured at a temperature of 30°C and a concentration of 0.5g / 100mL of 0.2 or more, preferably 0.4 or more, more preferably 0.6 or more, and even more preferably 0.7 or more. By setting the logarithmic viscosity within the above range, it may be possible to obtain a polyimide having a high molecular weight of polyamic acid and / or polyimide and mechanical properties suitable for use as a binder. The weight average molecular weight determined by gel permeation chromatography (GPC) is preferably 1,000 to 1,000,000, particularly 5,000 to 500,000. In detail, the weight average molecular weight is, for example, 1,000 or more, preferably 5,000 or more, more preferably 7,500 or more, and even more preferably 9,000 or more, and is, for example, 1,000,000 or less, preferably 500,000 or less, more preferably 300,000 or less, more preferably 100,000 or less, more preferably 50,000 or less, and even more preferably 30,000 or less. These logarithmic viscosity and molecular weight can be arbitrarily set by adjusting the molar ratio of the tetracarboxylic acid component and the diamine component used, and may be appropriately set in consideration of the mechanical strength of the negative electrode active material layer, the desired characteristics of the power storage device, the intended use, and the like. In the present invention, the polyamic acid and / or polyimide have a sufficiently high molecular weight that they can function even in a small amount. Examples of products (polyimide precursor compositions; varnishes) containing polyamic acids and / or polyimides having the above molecular weights include UPIA (registered trademark)-LB-1001 and UPIA (registered trademark)-LB-2001 manufactured by Ube Industries, Ltd.
[0027] When the precursor is a polyamic acid, the polyamic acid can be easily prepared by reacting a tetracarboxylic acid component with a diamine component in a solvent according to a known method. When the polyimide-based binder used in the present invention is a polyimide, the polyimide is preferably prepared by adding a tetracarboxylic acid component all at once or in multiple stages to a solution in which a diamine component is dissolved in a solvent, and then polymerizing (imidizing reaction) by heating or adding a catalyst or chemical imidizing agent.
[0028] The amount of polyimide-based binder may be an amount that does not inhibit the formation of a negative electrode active material layer having a specific range of porosity when the electrode mixture paste for the negative electrode of the electric storage device of the present invention is used to form the negative electrode active material layer on the current collector. For example, the polyimide-based binder (solid content of precursor) is 0.5% by mass to 50% by mass, preferably 1% by mass to 45% by mass, based on the total solid content of the electrode mixture paste for the negative electrode of the electric storage device. The upper limit can be more preferably 30% by mass or less, more preferably less than 20% by mass, more preferably less than 10% by mass, and more preferably less than 5% by mass. In the present invention, a small amount of binder (solid content) can fully exert the binder function, and as a result, the effects of the present application, such as high discharge capacity and excellent cycle characteristics, can be achieved. It is presumed that the use of polyamic acid and / or polyimide having a high molecular weight is one of the reasons for the excellent effects of the present application. The solid content of the precursor means the mass when completely imidized.
[0029] (Negative electrode active material) The negative electrode active material layer of the present invention contains a negative electrode active material that includes silicon-based particles. The silicon-based particles in the present invention are particles that contain silicon as a component and can absorb and release lithium ions. Examples of silicon-based particles include silicon, silicon-metal composites (including alloys of silicon and other metals), silicon oxide, silicon-silicon dioxide composites, etc., which may be used alone or in combination of two or more.
[0030] The shape of the negative electrode active material is not particularly limited, and may be any shape such as amorphous, spherical, fibrous, etc. The average particle size of the negative electrode active material is preferably less than 10 μm, and from the viewpoint of ensuring better cycle characteristics, it is preferably 5 μm or less. The average particle size is, for example, 0.01 μm or more. The negative electrode active material having such an average particle size may be one type, or may be one in which the average particle size is adjusted by mixing two or more types. Here, the average particle size is a value related to the primary particles of the silicon-based particles that are the negative electrode active material, and refers to the average particle size of the silicon-based particle powder, which can be measured, for example, by a laser diffraction type particle size distribution measuring device. Note that this average particle size may be confirmed from a scanning electron microscope (SEM) image of the surface of a negative electrode produced using the silicon-based negative electrode active material. When the particles are not spherical, the particle size refers to the longest part (major axis) of the particle.
[0031] In this way, the negative electrode active material can be used by appropriately combining the components, shapes and / or average particle diameters of silicon-based particles depending on the desired charge / discharge capacity and other characteristics of the electricity storage device.
[0032] In addition, the negative electrode active material of the present invention may contain other active materials other than silicon-based particles as necessary. As the other active materials, known active materials other than silicon-based particles can be used, for example, graphite particles such as natural graphite and artificial graphite, metals such as tin, germanium, antimony silver, copper, nickel, and the like, and particles of their alloys, etc. The average particle size of these other active materials is not particularly limited, but is preferably 5 μm or less. The blending ratio of the silicon-based particles to the other active materials is not particularly limited, and may be appropriately added in consideration of the charge / discharge capacity and other characteristics of the electricity storage device. In one embodiment, however, the amount of the other active materials (particularly the graphite particles) added is preferably 15 mass % or less, more preferably 10 mass % or less, and even more preferably 5 mass % or less, based on the total negative electrode active material. It is also preferable that no other active materials other than the silicon-based particles are included.
[0033] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited as long as it functions as a negative electrode active material layer. Usually, the content is 0.1 to 1000 times, preferably 1 to 1000 times, more preferably 5 to 1000 times, and even more preferably 10 to 1000 times, based on mass, relative to the polyimide-based binder. The upper limit is preferably 500 times or less, more preferably 100 times or less, and even more preferably 50 times or less. If the amount of the negative electrode active material is too large, the negative electrode active material is not sufficiently bound to the current collector and is likely to fall off. On the other hand, if the amount of the negative electrode active material is too small, the negative electrode active material layer formed on the current collector has many inactive parts, which may result in insufficient function as a negative electrode for a power storage device.
[0034] (porosity) In the present invention, the porosity of the negative electrode active material layer is less than 20%, preferably 18% or less, more preferably 15% or less. The porosity is at least 3% or more, preferably 5% or more. By setting the porosity as described above, it is possible to increase the lithium conduction rate, and the cycle characteristics, output characteristics, etc. are improved.
[0035] Here, the porosity in the present invention is a value calculated from the apparent density of the negative electrode active material layer and the true density (specific gravity) and blending amount of each component constituting the negative electrode active material layer (for example, the negative electrode active material (silicon-based particles), the polyimide-based binder, any material (other active material, polymer-based binder, etc.)). Specifically, it can be calculated by the following mathematical formula 1.
[0036] (Formula 1) Porosity (%)=100-N(WA1 / D A1 +W A2 / D A2 +···W An / D An +W B1 / D B1 +W B2 / D B2 +···+W Bm / D Bm )
[0037] For example, the negative electrode active material (true density D A1 (g / cm 3 )) to W A1 Mass%, other active materials (true density D A2 (g / cm 3 )) to W A2 Mass%, polyimide binder (true density D B1 (g / cm 3 )) to W B1 Mass %, other polymer binders (true density D B2 (g / cm 3 )) to W B2 The apparent density of the negative electrode active material layer mixed in mass% is N (g / cm 3 ) the porosity (%) is calculated using the following formula:
[0038] (Formula 2) Porosity (%)=100-N(W A1 / D A1 +W A2 / D A2 +W B1 / D B1 +W B2 / D B2 ) In addition, when two or more kinds of polyimide-based binders are used, the true density and mass of each component must be considered. Similarly, other active materials and other polymers must be considered for each component. As shown in this example, by satisfying the porosity specified in the present invention, it is possible to provide both high capacity and excellent cycle characteristics.
[0039] (Polymer-based binder) In the present invention, a polymer binder other than the polyimide binder may be included. Such a polymer binder is not particularly limited as long as it does not inhibit the functions of the polyimide binder and the negative electrode active material, and examples thereof include anionic polymers such as poly(meth)acrylic acid, polysulfonic acid, and salts thereof, water-soluble cellulose derivatives such as carboxyalkyl cellulose and hydroxyalkyl cellulose, water-soluble polymers such as polyvinyl alcohol, polyalkylene glycol, polyvinylpyrrolidone, salts thereof, and alginates, acrylic resins, synthetic rubbers, polyamides, silicone resins (including silicone oils), etc. In addition, it is not limited to these, and known electrode binders can also be used.
[0040] The polymer binder other than the polyimide binder may be selected and used in one or more types according to the function to be imparted to the negative electrode active material layer, the electricity storage device, etc. Also, according to the solvent to be used, a water-soluble polymer can be selected for an aqueous solvent system, and a polymer soluble in an organic solvent can be selected for an organic solvent system. The content of the polymer binder other than the polyimide binder (solid content of the precursor) can be appropriately set according to the purpose. For example, the amount of the other polymer binder is 0 to 1000 parts by mass (10 times the amount) with respect to 100 parts by mass of the polyimide binder (solid content of the precursor). In one embodiment, the amount of the other polymer binder is 50 parts by mass or less, preferably 20 parts by mass or less, and it is also preferable that no polymer binder other than the polyimide binder is contained (0 parts by mass). In a different embodiment, the amount of the other polymer binder is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, and may be, for example, 300 parts by mass or less, per 100 parts by mass of the polyimide binder (solid content of precursor).
[0041] (Conductive assistant) The negative electrode active material layer of the present invention may contain a conductive assistant as necessary. As such a conductive assistant, a conventionally known conductive assistant can be used, and one or more types can be used depending on the characteristics of the target negative electrode active material layer or the electric storage device. As such a conductive assistant, there is no particular limitation as long as it is a conventionally known conductive assistant, and for example, a carbon-based conductive assistant such as graphite, acetylene black, carbon black, or a metal-based conductive assistant such as silver, copper, nickel, or an alloy thereof can be used. As described above, in one embodiment of the present invention, it is preferable that the amount of active material other than silicon-based particles is small or that it is not contained, and in that case, it is preferable to use a material that does not occlude lithium in particles, such as acetylene black or carbon black, rather than a material having a charge / discharge capacity such as graphite.
[0042] (optional ingredient) The negative electrode active material layer of the present invention may contain other additives as necessary. The other additives may be used within a range that does not impair the effects of the present invention, and specifically include catalysts (e.g., amine compounds, imidazole compounds); chemical imidizing agents (e.g., acid anhydrides such as acetic anhydride, and amine compounds such as pyridine and isoquinoline); antioxidants (e.g., phenolic and phosphorus-based antioxidants); light stabilizers (e.g., hindered amine stabilizers); antistatic agents (e.g., surfactants, carbon, metal oxides); plasticizers (e.g., ester-based plasticizers, epoxidized vegetable oils); oil-soluble solvents (e.g., 1-acetonaphthone, Acetophenone, benzylacetone, methylacetophenone, dimethylacetophenone, propiophenone, valerophenone, anisole, methyl benzoate, benzyl benzoate); rust inhibitors (e.g., zinc compounds, lead compounds, diphenylamine, etc., adipic acid, ethanolamine and monoethanolamine, ethylene glycol monoethyl ether, trimethylamine, nonylphenol, hexamethylenediamine, pentaerythritol, etc., dicyclohexylammonium nitrite, diisopropylammonium nitrite light and mixtures thereof, dicyclohexylammonium caprate, laurate, carbonate, etc., benzotriazole and alkylbenzotriazole, amine salts, lower fatty acids and their salts, etc.; silane coupling agents; titanium coupling agents; flame retardants (e.g., bromine-based flame retardants, phosphorus-based flame retardants, antimony oxide, aluminum hydroxide, etc.); defoamers (e.g., silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers); leveling agents (e.g., silicone-based leveling agents, acrylic-based leveling agents); Leveling agents (e.g., benzyl alcohol, 2-phenylethyl alcohol, 4-methylbenzyl alcohol, 4-methoxybenzyl alcohol, 4-chlorobenzyl alcohol, 4-nitrobenzyl alcohol, phenoxy-2-ethanol, cinnamyl alcohol, furfuryl alcohol and naphthyl carbinol polyethylene glycol, coumarin, 2-butyne-1,4-diol, 2-propyn-1-ol, 3-phenylpropionic acid, etc.); rheology control agents (additives for flow control); viscosity modifiers; release agents;Examples of the surfactant include surfactants (e.g., anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants); metal soaps (e.g., salts of fatty acids such as stearic acid, lauric acid, ricinoleic acid, and octylic acid with metals such as lithium, magnesium, calcium, barium, and zinc); and supporting electrolytes (e.g., halides and nitrates of alkali metals, and salts of strong acids such as tetraalkylammonium perchlorates and tetrafluoroboric acid).
[0043] The thickness of the negative electrode active material layer of the present invention can be appropriately set according to the characteristics or shape of the target negative electrode or electricity storage device. For example, it can be about 0.5 μm to 300 μm, and preferably 1 μm or more. The thickness of the negative electrode active material layer is preferably 50 μm or less, more preferably 30 μm or less.
[0044] <<Electrode mixture paste for negative electrodes of electricity storage devices>> The electrode mixture paste for an electricity storage device negative electrode, which is one embodiment of the present invention, is used to form the above-mentioned negative electrode active material layer. This electrode mixture paste for the negative electrode of a storage device contains a negative electrode active material, a polyimide-based binder, and other optional components. For each of these components, the same ones as those disclosed in the section on the negative electrode active material layer above may be used. Furthermore, the electrode mixture paste for the negative electrode of a storage device of the present invention may contain various additives as necessary.
[0045] (solvent) The electrode mixture paste for the negative electrode of the electric storage device of the present invention may contain a solvent as necessary. Such a solvent can be appropriately selected according to the target electric storage device, electrode mixture paste, etc., and for example, an organic solvent, an aqueous solvent (water or a solvent containing water), or a mixture thereof can be used. Among them, a solvent used in preparing a polyimide-based binder (polyamic acid, polyimide resin, etc.) can be preferably used.
[0046] The organic solvent is not particularly limited, but examples thereof include amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and N-vinyl-2-pyrrolidone; cyclic ester solvents such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, ε-caprolactone, and α-methyl-γ-butyrolactone; carbonate solvents such as ethylene carbonate and propylene carbonate; glycol-based solvents such as triethylene glycol; phenol-based solvents such as phenol, o-cresol, m-cresol, p-cresol, 3-chlorophenol, and 4-chlorophenol; acetophenone, 1,3-dimethyl-2-imidazolidinone, sulfolane, and dimethyl sulfoxide. Further, for example, alcohol solvents such as methanol and ethanol, ester solvents such as butyl acetate, ethyl acetate, isobutyl acetate, ethyl propionate, ethyl butyrate, butyl butyrate, butyl benzoate, ethyl benzoate, and methyl benzoate, propylene glycol methyl acetate, ethyl cellosolve, butyl cellosolve, 2-methyl cellosolve acetate, ethyl cellosolve acetate, butyl cellosolve acetate, tetrahydrofuran, dimethoxyethane, diethoxyethane, dibutyl ether, diethylene glycol dimethyl ether, methyl isobutyl ketone, diisobutyl ketone, cyclopentanone, cyclohexane ... Other common organic solvents include hexanone, methyl ethyl ketone, acetone, butanol, ethanol, xylene, toluene, chlorobenzene, N-methylcaprolactam, hexamethylphosphorotriamide, bis(2-methoxyethyl)ether, 1,2-bis(2-methoxyethoxy)ethane, bis[2-(2-methoxyethoxy)ethyl]ether, 1,4-dioxane, dimethyl sulfoxide, dimethyl sulfone, diphenyl ether, diphenyl sulfone, tetramethylurea, anisole, turpentine, mineral spirits, petroleum naphtha solvents, biodegradable methyl lactate, ethyl lactate, butyl lactate, and other common organic solvents. The organic solvent used may be one type or two or more types.
[0047] The electrode mixture paste for the negative electrode of the electricity storage device of the present invention can be prepared by a general preparation method, such as a method of mixing a negative electrode active material with a polyimide binder at a moderate temperature range (preferably 10°C to 60°C).
[0048] <<Method of manufacturing the negative electrode active material layer>> The method for producing the negative electrode active material layer, which is one embodiment of the present invention, is not particularly limited as long as it can produce the desired negative electrode active material layer. One example is a method in which an electrode mixture paste for a negative electrode of a power storage device is cast or applied onto a current collector and then heated to form a negative electrode active material layer. Note that polyamic acid can easily be converted into polyimide by heat treatment or chemical treatment with an imidizing agent or the like. Below, the method for producing the negative electrode active material layer will be described in detail along this example.
[0049] The current collector used in the present invention can be an electronic conductor that does not undergo general chemical changes. Examples of materials that form these current collectors include aluminum, copper, copper alloys, iron, stainless steel, nickel, and titanium, and aluminum, copper, copper alloys, iron, and stainless steel surfaces treated with carbon, nickel, titanium, silver, and the like (thin films formed thereon) can also be used. Among these, aluminum, copper, copper alloys, nickel-plated steel, stainless steel, and the like can be preferably used.
[0050] The current collector is usually in the form of a foil (sheet), but a net, a punched material, a porous material, a molded body of a fiber group, etc. may also be used depending on the intended electricity storage device. The current collector may also be one having an uneven surface provided by a surface treatment.
[0051] The thickness of the current collector is not particularly limited, and can be usually 1 μm to 500 μm. In the present invention, metal foils such as copper foil, stainless steel foil, nickel foil, etc. can be preferably used as the current collector, and among them, copper foils such as electrolytic copper foil and rolled copper foil can be preferably used. The thickness of these metal foils is not particularly limited, and can be usually 5 to 50 μm, preferably 9 to 18 μm.
[0052] When a metal foil is used as the current collector, the surface of the foil may be roughened or rust-proofed to improve adhesion. A conductive adhesive layer may be laminated on the surface of the foil. The conductive adhesive layer can be formed by blending conductive particles such as graphite with an organic polymer compound.
[0053] The electrode mixture paste for the negative electrode of the electricity storage device can be applied to the current collector by a continuous roll-to-roll application method or a sheet-by-sheet application method, and examples of the application device that can be used include a die coater, a multi-layer die coater, a gravure coater, a comma coater, a reverse roll coater, and a doctor blade coater.
[0054] The heat treatment is preferably carried out under conditions that can remove the solvent contained in the electrode mixture paste for the negative electrode of the power storage device, melt or imidize the polyimide binder, integrate it with other components (e.g., the negative electrode active material, etc.) that form the negative electrode active material layer, and bond the current collector and the negative electrode active material layer, etc. For example, it is preferable to carry out the heat treatment at a temperature equal to or higher than the melting point of the polyimide binder used, and under pressure as necessary. The heat treatment may be carried out only once or may be carried out multiple times.
[0055] The heat treatment temperature is not particularly limited as long as it is a condition under which a negative electrode active material layer can be produced, and can be appropriately set according to the type of polyimide-based binder (precursor) contained in the electrode mixture paste for the negative electrode of the power storage device used, the type of solvent, and the like. The heat treatment temperature is, for example, preferably 80°C to 350°C, more preferably 100°C to 300°C, and particularly preferably 120°C to 250°C. If the heat treatment temperature is lower than 80°C, a long time may be required to remove the solvent, and insufficient melting and slow imidization reaction are not preferable, and if it is higher than 350°C, deterioration of the current collector, polyimide-based binder, and / or polymer-based binder, etc., occurs, which is not preferable. The heat treatment may be performed in multiple stages to increase the temperature in order to prevent foaming and powdering.
[0056] The heat treatment time is not particularly limited as long as the desired negative electrode active material layer can be produced, but can be set in the range of, for example, 3 minutes to 48 hours. The above range allows the imidization reaction and removal of the solvent to be carried out sufficiently, and is also preferable from the viewpoint of productivity. During this time, most of the solvent is removed, and the polyamic acid is substantially converted into polyimide by the imidization reaction.
[0057] In the present invention, a pressurizing step may be added. For example, pressurizing may be applied before heat treatment, after heat treatment, or simultaneously with heat treatment. In addition, when heat treatment is performed multiple times, pressurizing may be applied between heat treatments. Specific pressurizing conditions and pressurizing means are not particularly limited, but for example, a method of pressing with a linear pressure of 100 to 2000 kg / cm using a roll press machine may be mentioned. Here, the porosity in the negative electrode active material layer should be appropriately adjusted depending on the types of constituent components such as polyimide binder and negative electrode active material, and the necessary pressurizing conditions are appropriately controlled so that the porosity becomes a desired value, taking into consideration the types of each constituent component.
[0058] The porosity, which is one of the constituent elements of the present invention, tends to decrease as the applied pressure increases, but this tendency can be used as an indicator to adjust the manufacturing conditions. It can also be fine-tuned by adjusting detailed conditions such as heat shrinkage and crosslink density.
[0059] When the negative electrode active material layer of the present invention is evaluated under the conditions of the examples described later, the capacity retention rate calculated by (discharge capacity after cycle test)÷(initial discharge capacity) is preferably more than 50%, more preferably 75% or more. When evaluated under the same conditions, the initial charge-discharge efficiency calculated by (initial discharge capacity)÷(initial charge capacity) is preferably more than 81%, more preferably 89% or more.
[0060] <<Negative electrodes for electricity storage devices>> The negative electrode for an electricity storage device, which is one embodiment of the present invention, has the above-mentioned negative electrode active material layer. More specifically, the negative electrode for an electricity storage device has the negative electrode active material layer of the present invention on a current collector. As described above, a method for producing the negative electrode for an electricity storage device may be adopted in which a negative electrode active material layer is formed on a current collector. In addition, the negative electrode for an electricity storage device may have one or more types of various functional layers laminated on the negative electrode active material layer depending on the aspect of the electricity storage device.
[0061] <<Electricity storage devices>> The electric storage device according to one embodiment of the present invention includes an electric storage device negative electrode having the above-mentioned negative electrode active material layer. The above-mentioned electric storage device negative electrode of the present invention can be suitably made into an electric storage device according to a known method. For example, the obtained electric storage device negative electrode and positive electrode are wound into a cylindrical shape while sandwiching a separator such as a polyolefin porous body, and the cylindrical electrode body is left as it is or is crushed to be flattened, and the electrode body and a nonaqueous electrolyte are inserted into an exterior body, whereby an electric storage device can be suitably obtained.
[0062] The positive electrode in the present invention is a layer containing at least a positive electrode active material formed on a current collector. A general positive electrode active material can be used as the positive electrode active material. For example, lithium-containing composite metal oxide, olivine-type lithium salt, chalcogen compound, and manganese dioxide can be mentioned. The lithium-containing composite metal oxide is a metal oxide containing lithium and a transition metal, or a metal oxide in which a part of the transition metal in the metal oxide is replaced by a different element. Here, examples of the different element include Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, and Mn, Al, Co, Ni, and Mg are preferable. The different element may be one type or two or more types. Among these, lithium-containing composite metal oxides are preferable. Examples of the lithium-containing composite metal oxide include Li x CoO2, Li x NiO2, Li x MnO2, Li x Co y Ni 1-y O2, Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4, Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (in the above formulas, M represents at least one element selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, V, and B. x=0 to 1.2, y=0 to 0.9, and z=2.0 to 2.3). Here, the value of x representing the molar ratio of lithium increases or decreases by charging and discharging. In addition, an example of the olivine-type lithium salt is LiFePO4. An example of the chalcogen compound is titanium disulfide or molybdenum disulfide. The positive electrode active material can be used alone or in combination of two or more types. The current collector used in the positive electrode may be a commonly used one.
[0063] The non-aqueous electrolyte is not particularly limited as long as it is normally used in an electric storage device, and a non-aqueous solvent in which a lithium salt is dissolved is preferably used. Examples of the non-aqueous solvent include cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, chain carbonates such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate, aliphatic carboxylic acid esters such as methyl formate, methyl acetate, methyl propionate, and ethyl propionate, lactones such as γ-butyrolactone and γ-valerolactone, chain ethers such as 1,2-dimethoxyethane, 1,2-diethoxyethane, and ethoxymethoxyethane, and cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran. These can be used alone or in combination of two or more.
[0064] Examples of lithium salts that dissolve in non-aqueous solvents include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCl, LiCF3SO3, LiCF3CO2, Li(CF3SO2)2, LiAsF6, LiN(CF3SO2)2, LiB 10 Cl 10 Examples of the lithium salt include lithium carboxylates, lower aliphatic carboxylates, LiCl, LiBr, LiI, lithium chloroborane, lithium tetraphenylborate, and lithium imide salts. These can be used alone or in combination of two or more. The amount of the lithium salt dissolved in the non-aqueous solvent is not particularly limited, but is preferably 0.2 to 2 mol / L, and more preferably 0.5 to 1.5 mol / L.
[0065] In addition, various additives may be further added to the non-aqueous electrolyte for the purpose of improving the charge / discharge characteristics of the power storage device. Examples of such additives include vinylene carbonate, vinyl ethylene carbonate, phosphazene and fluorobenzene, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, pyridine, hexaphosphoric acid triamide, nitrobenzene derivatives, crown ethers, quaternary ammonium salts, and ethylene glycol dialkyl ethers. These additives are preferably mixed in an amount of about 0.5 to 10% by mass of the non-aqueous electrolyte.
[0066] In addition, in the present invention, an insulating microporous thin film that has been conventionally used in lithium ion batteries can be used as the separator. The microporous thin film preferably has a function of blocking pores at a certain temperature or higher and increasing resistance. As the material for the microporous thin film, polyolefins such as polypropylene and polyethylene, which have excellent organic solvent resistance and hydrophobicity, are preferably used. Sheets, nonwoven fabrics, woven fabrics, etc. made of glass fibers can also be used.
[0067] The shape of the electric storage device of the present invention is not particularly limited, and may be, for example, a coin type, a button type, a sheet type, a cylindrical type, a flat type, a square type, or the like. When the shape of the electric storage device is a coin type or a button type, the negative electrode mixture is mainly compressed into a pellet shape for use. The thickness and diameter of the pellet may be determined according to the size of the electric storage device. The wound electrode body in the present invention does not necessarily have to be a perfect cylinder, and may be an elongated cylinder with an elliptical cross section or a prismatic shape such as a rectangle.
[0068] The electricity storage device of the present invention has a high charge / discharge capacity and is provided with a negative electrode that can realize excellent cycle characteristics. Therefore, even in the form of a so-called all-solid-state battery that does not use an electrolyte, the device can fully exhibit its capabilities and can be suitably used. EXAMPLES
[0069] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0070] The abbreviations of the compounds used in the following examples are explained below. Polyimide-based binder (precursor composition): UPIA (registered trademark)-LB-1001 (polyamic acid varnish (solvent: NMP) manufactured by Ube Industries, Ltd.) NMP: N-methyl-2-pyrrolidone EC: Ethylene carbonate DEC: Diethyl carbonate
[0071] (1) Preparation of negative electrodes for evaluation Silicon (average particle size 5 μm) as the negative electrode active material, UPIA (registered trademark)-LB-1001, and acetylene black as the conductive assistant were mixed to a ratio of 80:2:18 (mass ratio; UPIA (registered trademark)-LB-1001 is the amount of solid content (polyimide precursor)), and NMP was added so that the slurry concentration became about 60 mass%, to prepare a negative electrode mixture paste for a power storage device. This negative electrode mixture paste for a power storage device was applied onto a nickel-plated steel foil (thickness 10 μm) as a current collector, and pre-dried at 80° C. for 10 minutes. Thereafter, it was roll-pressed, placed in a vacuum dryer, and heat-treated at 350° C. for 1 hour to produce a negative electrode for evaluation (capacity density: 3 mAh / cm 2 By changing the press line pressure, negative electrodes for evaluation having negative electrode active material layers with different porosities were prepared.
[0072] (2) Preparation of evaluation batteries Using the negative electrode for evaluation obtained in (1) above, a battery for evaluation was fabricated in the following configuration. Counter electrode: Lithium foil (metallic lithium) Electrolyte: 1M LiPF6 / EC:DEC=1:1 (volume%)
[0073] (3) Battery evaluation The battery was repeatedly charged and discharged under the following conditions to evaluate the cycle characteristics. ·Measurement temperature: 30℃ Charge / discharge range: SOC (battery charge rate) 30-90% Charge / discharge current value: 0.1C The initial charge / discharge efficiency was calculated by (initial discharge capacity) / (initial charge capacity). The capacity retention rate was calculated by (discharge capacity after cycle test)÷(initial discharge capacity). In this specification, the absorption of Li into the "negative electrode for evaluation" is referred to as "charging," and the release of Li from the "negative electrode for evaluation" is referred to as "discharging."
[0074] [Example 1] The charge-discharge cycle characteristics of the fabricated test battery (negative electrode active material layer porosity: 5%) were examined, and the capacity retention rate after 40 cycles was 95%. The initial charge-discharge efficiency was 90%.
[0075] [Example 2] The charge-discharge cycle characteristics of the fabricated test battery (negative electrode active material layer porosity: 10%) were examined, and the capacity retention rate after 40 cycles was 88%. The initial charge-discharge efficiency was 89%.
[0076] [Example 3] The charge-discharge cycle characteristics of the fabricated test battery (negative electrode active material layer porosity: 18%) were examined, and the capacity retention rate after 40 cycles was 75%. The initial charge-discharge efficiency was 94%.
[0077] [Comparative Example 1] The charge-discharge cycle characteristics of the fabricated evaluation battery (porosity of the negative electrode active material layer: 25%) were examined, and the capacity retention rate after 40 cycles was 50%. Also, the initial charge-discharge efficiency was 81%.
[0078] [Comparative Example 2] The charge-discharge cycle characteristics of the fabricated test battery (porosity of the negative electrode active material layer: 30%) were examined, and the capacity retention rate after 40 cycles was 44%. The initial charge-discharge efficiency was 67%.
[0079] [Comparative Example 3] The charge-discharge cycle characteristics of the fabricated test battery (porosity of the negative electrode active material layer: 35%) were examined, and the capacity retention rate after 40 cycles was 48%. The initial charge-discharge efficiency was 44%.
Claims
[Claim 1] Silicon-based particles that contain silicon as an ingredient and are capable of absorbing and releasing lithium ions; A polyimide binder, which is an organic polymer with imide bonds in the main chain, and having a porosity of less than 20%.
Citation Information
Patent Citations
Lithium secondary battery negative electrode and lithium secondary battery
JP2003203637A
Negative electrode for lithium secondary battery, and lithium secondary battery
JP2004022433A
Negative electrode for lithium secondary battery, and the battery
JP2004235057A
Negative electrode for lithium secondary battery and lithium secondary battery
JP2004288520A
Lithium secondary battery negative electrode and method for manufacturing the same
JP2017092048A